1997
DOI: 10.1016/s0960-9822(06)00260-0
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian homologues of C. elegans PAR-1 are asymmetrically localized in epithelial cells and may influence their polarity

Abstract: The establishment of polarity in the embryo is fundamental for the correct development of an organism [1]. The first cleavage of the Caenorhabditis elegans embryo is asymmetric with certain cytoplasmic components being distributed unequally between the daughter cells [2-4]. Using a genetic screen, Kemphues and co-workers have identified six par genes (partition-defective) [5,6], which are involved in the process of asymmetric division. One of these genes encodes a highly conserved protein, PAR-1, which is a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
117
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(125 citation statements)
references
References 13 publications
7
117
0
1
Order By: Relevance
“…These k ex values indicate that exchange occurs in the fast limit [i.e., k ex Ͼ Ͼ ␦ , where ␦ ϭ N *␦ , ␦ , and ␦ are frequency (rad/s) and chemical shift differences (ppm) between states, respectively, and N is Larmor frequency of the 15 N nucleus] so that neither the populations of the exchanging states nor the chemical shifts for each probe in each state could be reliably estimated. In this limit, it is only possible to extract the exchange rate constant k ex ϭ k A ϩ k B and the product p A p B (␦ ) 2 , where p A and p B are the fractional populations of interconverting sites A and B, respectively. In what follows, we have assumed that the populations of each state are equal (p A ϭ p B ϭ 0.5) so that the minimum chemical shift differences between each state, ␦ , could be obtained for each probe.…”
Section: Nmr Characterization Of the Putative Folding/unfolding Equilmentioning
confidence: 99%
See 1 more Smart Citation
“…These k ex values indicate that exchange occurs in the fast limit [i.e., k ex Ͼ Ͼ ␦ , where ␦ ϭ N *␦ , ␦ , and ␦ are frequency (rad/s) and chemical shift differences (ppm) between states, respectively, and N is Larmor frequency of the 15 N nucleus] so that neither the populations of the exchanging states nor the chemical shifts for each probe in each state could be reliably estimated. In this limit, it is only possible to extract the exchange rate constant k ex ϭ k A ϩ k B and the product p A p B (␦ ) 2 , where p A and p B are the fractional populations of interconverting sites A and B, respectively. In what follows, we have assumed that the populations of each state are equal (p A ϭ p B ϭ 0.5) so that the minimum chemical shift differences between each state, ␦ , could be obtained for each probe.…”
Section: Nmr Characterization Of the Putative Folding/unfolding Equilmentioning
confidence: 99%
“…P rotein kinases in the Par-1/MARK family are the subject of intense interest because of the crucial roles they play in establishing cell polarity (1)(2)(3)(4), regulating the cell cycle progression (5)(6)(7), and controlling microtubule dynamics (8)(9)(10)(11). Functional orthologs of Par-1 have been described from yeast to mammals (1-3, 8, 12).…”
mentioning
confidence: 99%
“…In mammals, there are several Par1-related proteins (Tassan and Le Goff, 2004), and Par1b is the best characterized. The polarity-regulating function of Par1 is evolutionarily conserved, and it has been shown that Par1 is important in the regulation of apical-basolateral polarity of epithelial cells (Bohm et al, 1997;Cohen et al, 2004a,b;Hurov et al, 2004;Suzuki et al, 2004). Illenberger et al (1996) discovered the serine/threonine kinase microtubule affinity regulating kinase (MARK) as an ortholog of C. elegans Par1, which phosphorylates several microtubule-binding proteins (MAPs).…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian epithelial cells, Par1/MARK localizes predominantly at basolateral membranes and is excluded from apical areas (Bohm et al, 1997). Par1/MARK is phosphorylated by atypical protein kinase C (aPKC) (Hurov et al, 2004;Kusakabe and Nishida, 2004;Suzuki et al, 2004), and then moves to the cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…Originally identified in Caenorhabdhitis elegans as a critical player in early embryonic polarity, Par-1 has since been shown to regulate cell polarity in yeast, Drosophila, Xenopus, and several mammalian cell types (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Par-1 is a regulator of microtubule stability, the Wnt signaling pathway and also plays a role in vesicular trafficking (2,8,12,(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%